2002
DOI: 10.1172/jci0216588
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Cdk inhibitor p21 by LY83583 inhibits tumor cell proliferation in a p53-independent manner

Abstract: Conflict of interest:The authors have declared that no conflict of interest exists. Nonstandard abbreviations used: human diploid fibroblast (HDF); 6-anilino-5,8-quinolinequinone (LY83583); LY83583 (LY); mouse embryo fibroblasts (MEFs); elongation factor 1α (ELF1α); soluble guanylate cyclase β3 (sGC-β3); quantitative real-time PCR (qPCR); crossing point (CP); propidium iodide (PI); sodium nitroprusside (SNP); senescence-associated β-galactosidase (SA-β-gal); bromodeoxyuridine (BrdU); soluble guanylate cyclase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…NO has also been shown to inhibit cell motility and invasion by inducing tumor suppressor maspin in breast cancer cells (27). sGC which functions as a NO sensor has been shown to promote angiogenesis in endothelial cells (14) whereas, a nonspecific sGC inhibitor LY83583 inhibits tumor cell growth by induction of a cdk inhibitor p21 in a p53-independent manner in colorectal, breast and malignant melanoma cell lines (28). Similarly another sGC inhibitor ODQ has been shown to exert anti-tumor effect with prostate cancer cell lines in a cGMP independent manner (29).…”
Section: Discussionmentioning
confidence: 99%
“…NO has also been shown to inhibit cell motility and invasion by inducing tumor suppressor maspin in breast cancer cells (27). sGC which functions as a NO sensor has been shown to promote angiogenesis in endothelial cells (14) whereas, a nonspecific sGC inhibitor LY83583 inhibits tumor cell growth by induction of a cdk inhibitor p21 in a p53-independent manner in colorectal, breast and malignant melanoma cell lines (28). Similarly another sGC inhibitor ODQ has been shown to exert anti-tumor effect with prostate cancer cell lines in a cGMP independent manner (29).…”
Section: Discussionmentioning
confidence: 99%
“…The latter is currently being studied in clinical trials for patients with AML. GUCY1A3, which encodes a component of the soluble guanylate cyclase enzyme catalyzing the conversion of GTP to cGMP, is repressed during replicative senescence 42 , and cGMP has been reported to stimulate HSC proliferation 43 .…”
Section: Commentmentioning
confidence: 99%
“…Treatment with 6-anilino-5,8-quinoline quinone, a previously described inhibitor of guanylate cyclase, induced cellular senescence [112]. Microarray analysis revealed that this compound induced the Cdk inhibitor p21WAF1 in a p53-independent manner.…”
Section: Senescence-based Therapymentioning
confidence: 99%